PERANAN MIKROORGANISME ENDOFIT DALAM DUNIA KESEHATAN: KAJIAN PUSTAKA (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2019)
The infection disease is still important problem in Indonesia, especially in eastern part of Indonesia. The problem of the bacterial resistance has resulted in increased morbidity, mortality, and costs of healthcare. This situation is therefore drives many researches on discovery for new antibiotics and novel bioactive compounds to combat multidrug resistant microbes, such as Mycobacterium tuberculosis, Staphylococcus spp., and Streptococcus spp. Â The aim of this study is to know the development of the endophytic microorganisms. The endophytic bacteria provide vast potential in producing various novel natural products, including secondary metabolites similar to their hosts. The plant is one of host for the endophytic microorganisms reside. In Indonesia, that endophytic is used medicinally for treatment as well as from the host. The bioactive compound of endophytic microorganisms are used medicinally for treatment antibacterial, antiviral, anticancer, antioxidants, antidiabetic, and immunosuppressive. These showed that endophytic bacteria are promising source of new antibiotics against susceptible and resistant forms of various infectious microbes.